2012
DOI: 10.1097/cji.0b013e3182585d50
|View full text |Cite
|
Sign up to set email alerts
|

A Cytomegalovirus-based Vaccine Expressing a Single Tumor-specific CD8+ T-cell Epitope Delays Tumor Growth in a Murine Model of Prostate Cancer

Abstract: Cytomegalovirus (CMV) is a highly immunogenic virus that results in a persistent, life-long infection in the host typically with no ill-effects. Certain unique features of CMV, including its capacity to actively replicate in the presence of strong host CMV-specific immunity, may give CMV an advantage compared to other virus-based vaccine delivery platforms. In the present study, we tested the utility of mouse CMV (mCMV)-based vaccines expressing human prostate-specific antigen (PSA) for prostate cancer immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 51 publications
1
53
1
Order By: Relevance
“…Given that high titer primary infection and reinfection might contribute significantly to these phenomena, strategies to reduce primary or prevent reinfection might be desirable. In addition, there is growing interest in using CMV as a vaccine vector for other diseases [37, 7881]. Given the widespread prevalence of CMV in the population, many of these vaccines would require reinfection of naturally infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Given that high titer primary infection and reinfection might contribute significantly to these phenomena, strategies to reduce primary or prevent reinfection might be desirable. In addition, there is growing interest in using CMV as a vaccine vector for other diseases [37, 7881]. Given the widespread prevalence of CMV in the population, many of these vaccines would require reinfection of naturally infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…CMV-based vectors have shown promising results in diverse infectious and cancer models, but the success of these vaccines is considered T cell mediated (5,55,56). Recently, it has been shown that CMV vectors encoding additional antigens also can induce protective anti-melanoma or anti-tetanus toxin antibodies (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…12, 14, 15, 16, 17, 18 Similar vectors have been evaluated for therapeutic utility against cancer leading to delayed growth or rejection of tumors and even for the purpose of immunocontraception in mice. 19, 20, 21 …”
Section: Introductionmentioning
confidence: 99%